In Situ Hydrogenation of CO2 by Al/Fe and Zn/Cu Alloy Catalysts under Mild Conditions. Issue 6 (12th April 2019) - Sun, Yufan; Hu, Hanjun; Wang, Yutian; Gao, Jia; Tang, Yang; Wan, Pingyu; Hu, Qing; Lv, Jianjun; Zhang, Tianshu; Yang, Xiao Jin
Abstract: The development of efficient metal catalysts for in situ hydrogenation of CO2 in water under mild conditions has gained considerable attention. Three Al alloys (Al/Fe, Al/Fe/Cu, Al/Cu) and three Zn/Cu alloys for in situ hydrogenation of CO2 in aqueous bicarbonate solutions were investigated. Hydrogen was generated by reaction of Al, Fe, and Zn in the alloys with water. In situ hydrogenation of CO2 was likely to be catalyzed by intermetallic compounds and generated metal oxides. Al alloys catalyzed the hydrogenation to methane while Zn/Cu alloys produced CO and formic acid. Zn/Cu5 possessed the highest catalytic activity, which was attributed to the CuZn5 crystal planes in the alloys. Insights are provided into the importance of compositions and structures of alloys for the selectivity for in situ hydrogenation of CO2 in aqueous bicarbonate solutions. Abstract : Under mild hydrothermal conditions, CO2 was in situ hydrogenated to CH4 by Al/Fe, Al/Fe/Cu, and Al/Cu alloys and to CO and HCOOH by a Zn/Cu alloy. Zn/Cu exhibited the greatest catalytic activity for both in situ generation of H2 and production of CO and HCOOH. The high performance of the Zn/Cu catalyst was likely attributed to the CuZn5 crystal planes in the alloy.